Bahan Ajar Ebook dengan Perspektif Sejarah Lokal Kota Padang - Rahfit Syahputra; Ridho Bayu Yefterson (Jurnal Kronologi, 2021)
Historical learning can actually make students think critically and have the skills to think cause and effect to understand a historical event. One way that can be done to make history learning more meaningful is by innovating teaching materials into digital teaching materials in which there are contextual materials such as local history and containing supporting media including pictures and videos. This study aims (1) to describe the stages of the development of e-book teaching materials for Indonesian history subjects in the perspective of local history in the city of Padang in order to practice causal thinking skills. (2) To test and describe the feasibility of e-book teaching materials for Indonesian history subjects in the perspective of local history in Padang City which was developed in order to train causal thinking skills. (3) To describe the practicality of e-book teaching materials for Indonesian history subjects in the perspective of local history in Padang City which was developed in order to train the ability to think cause and effect. The method in this research is the method of research and development or R&D. Researchers used the ADDIE model in developing e-book teaching materials in the perspective of the local history of Padang City but it was trimmed down to ADDI so that this research stage only reached the implementation stage. The results showed that the material "Resistance against the Allies Comes to Indonesia" in this case the Battle of Surabaya and the local context of the Battle of the Padang Area is very suitable to be used to train students' causal thinking skills. The evaluation of e-book teaching materials experts from the perspective of local history in Padang City also shows that the teaching materials developed are very suitable to be used to train causal thinking skills as well as teaching materials in history learning. The practicality of the teacher shows that e-book teaching materials from the perspective of local history in Padang City are very practical to be used as teaching materials in learning Indonesian history and training the ability to think cause and effect. Keywords: E-book Teaching Materials, Local History, Thinking Cause and Effect, History Learning